Exploring ESL public speaking anxiety among undergraduates / Ch’ng Looi Chin, Chan Ai Nyet and Noor Ain Saufi - Ch’ng, Looi Chin; Chan, Ai Nyet; Saufi, Noor Ain
English is a core subject in Malaysian schools, yet many students struggle with spoken English despite receiving at least eleven years of formal education. Challenges such as limited fluency, difficulty in organizing ideas, and fear of making mistakes often contribute to anxiety in oral communication. This study explores public speaking anxiety among undergraduate ESL learners, focusing on three key areas: specific anxiety-inducing situations, overall anxiety levels, and the factors contributing to these anxieties. Data were collected from 65 undergraduate students from Universiti Teknologi MARA, using a mixed-methods approach. Thematic analysis was employed to examine common anxiety-inducing situations, such as fear of making mistakes, negative feedback, and unpreparedness. In addition, the study employed the Public Speaking Classroom Anxiety Scale (PSCAS) to evaluate the students' anxiety levels and identify key contributors to their anxiety. The findings revealed that Fear of Negative Evaluation and Communication Apprehension were significant factors, while Comfort in Speaking English was moderate. Test Anxiety was the least impactful. The study highlights the need for targeted interventions to reduce anxiety and foster confidence in oral communication, with suggestions for more supportive learning environments that reduce fear and build students' comfort levels. The findings offer valuable insights for educators and curriculum designers aiming to create more effective strategies to help students overcome public speaking anxiety and improve their spoken English skills.